2021
DOI: 10.1101/2021.03.01.433120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced ER-mitochondria connectivity promotes neuroblastoma multidrug resistance

Abstract: Most cancer deaths result from progression of therapy resistant disease, yet our understanding of this phenotype is limited. Cancer therapies generate stress signals that act upon mitochondria to initiate apoptotic programs. We isolated mitochondria from neuroblastoma cell lines obtained from children at diagnosis and after relapse following failed therapy, and profiled responses to tBid and Bim, death effectors activated by therapeutic stress. Mitochondria from post-relapse models had markedly attenuated cyto… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…1f). This is in line with our previous findings demonstrating that CHLA-20 has diminished sensitivity to apoptosis induction directly at the level of isolated mitochondria [13]. Together, the CHLA-15/CHLA-20 pair represents a useful model of emergent therapy resistance and cancer stemness in neuroblastoma.…”
Section: Mitochondria-targeting Inhibitors Overcome Emergent Multidru...supporting
confidence: 91%
See 2 more Smart Citations
“…1f). This is in line with our previous findings demonstrating that CHLA-20 has diminished sensitivity to apoptosis induction directly at the level of isolated mitochondria [13]. Together, the CHLA-15/CHLA-20 pair represents a useful model of emergent therapy resistance and cancer stemness in neuroblastoma.…”
Section: Mitochondria-targeting Inhibitors Overcome Emergent Multidru...supporting
confidence: 91%
“…Previously, CHLA-20 cells were reported more resistant to diverse chemotherapeutics than CHLA-15 [13,22]. Validating this phenotype in our experimental settings, CHLA-20 cells exhibited broad resistance (1.6-fold to 44.5-fold difference vs. CHLA-15) to both DNA and non-DNA targeting drugs.…”
Section: Mitochondria-targeting Inhibitors Overcome Emergent Multidru...supporting
confidence: 63%
See 1 more Smart Citation
“…There are existing reports that establish the crosstalk between ER and mitochondria. According to Sassano et al, the first-ever inter-organelle contact site was discovered was the entanglement (mitochondria-associated membranes) between mitochondria and ER [30] , and they proposed that inter-organelle Ca +2 ion flow maintains their functionality [33] . Miscommunication between these organelles can lead to cellular bio-chemical dis-equilibrium shifting balance towards disorders [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the dysregulation of inter-organelle communication seems to play a crucial role in the onset of pathological conditions, membrane contact sites could also become an interesting and appealing pharmacological target. For example, recently, Coku et al, 2022 demonstrated that reduced ER–mitochondria crosstalk promotes multidrug resistance in neuroblastoma cells. Thus, testing the effect of different chemotherapeutic agents in modulating the contact sites of interest could be insightful.…”
Section: Proximity-driven Fluorescent Tools For Different Purposes: H...mentioning
confidence: 99%